SEJARAH KEPUNAHAN PALEOFLORA DJ KAWASAN KARST GUNUNGSEWU - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This research was conducted in the Gunungsewu karst area with the aimof (1) revew the paleoflora history in Gunungsdewu karst area, and (2) trace the causes of paleo flora extinction in this region. This research used the paleoecobotanyapproach to track paleoflora histrory during human prehistory in the karst region. The method used descriptive-explanatory, to explore and interpret the trace of paleoflora through pollen analysis and radiocarbon dating. Tracing sources of anthropogenic causes of human prehistory startingfrom Keplek, Ngrijangan to Klepu period. Analogy approach undertaken to assess the occupancy of paleoflora type. The result of temporranj pollen analysis and periodization of human prehistory be the basis for identifying the causes of paleoflora extinction and the sources. This research resulted information that paleoflora history in karst region has experienced three changes to three types paleoflora. T.e third type is montane flora type based on the finding of Altingia excelsa and Pinus sp. at 16.894t440 to 9.296:1:140 years BP (coinciding with the Keplek prehistry period), wet tropical flora based on the findings of Dipterocarpus sp., Durio sp., and Celtis sp.at 9.296:t140 hingga 1.753t90 to 689:t65 years BP (coinciding with the end ofKeplek prehistory period and up to Ngrijangan), and the type of monsoon flora based on the findings ofTaJ(,arindus indica, Ficus sp., Anacardium occidentale, and Swietenia sp. at 1.753t90 to 689:t65 years BP (coinciding with the end of the.Ngrijangan period up to Klepu), even up to now. Anthropogenic traces of human prehistory is subsistence culture and does not cause the paleoflora exticntion. Change the type of paleoflora explain the occurence of palaeoclimate variations, which have implications on its extinction because it can not adapt anymore. This reseach may expalin the variation of palaeoclimate, and found no cause of anthropogenic the source of human prehistory.